RANKING ECONOMIES BY CORRUPTION AND TECHNOLOGY TRANSFER ON FOREIGN DIRECT INVESTMENT BASIS - MARDIROS Daniela; DICU Roxana; AEVOAE George Marian (Annals of the University of Oradea: Economic Science, 2019)
The paper aims, for 2008-2018, a case study regarding the ranking of the European Union countries (Eastern Europe) by two indicators: corruption in the public sector and intensity of the technology transfer associated to the Foreign Direct Investment (FDI). We use in our research the quantitative analysis method. As data panel, we have the values of corruption and technology transfer intensity delivered by Transparency International, Corruption Perception Index, and World Economic Forum, Global Competitiveness Reports. The paper begins with the definition of the corruption and is followed by the presentation of certain elements used inside the methodology of the index used to measure it. The characterization of the Eastern European economies through the Corruption Perception Index is doubled by the exposure of the values associated with the intensity of the technology transfer related to Foreign Direct Investments. For the last item, the paper also presents the set of elements necessary to attract it and some correspondent public policies, created and implemented by the public sector authorities